Measurement of quarkonium production at forward rapidity in pp collisions at √s = 7 TeV = The ALICE Collaboration: B. Abelev, V. Anguelov, O. Busch, P. Glässel, J. Klein, D. Lohner, X.-G. Lu, A. Maire, J. Mercado Pérez, H. Oeschler, K. Oyama, Y. Pachmayer, K. Reygers, R. Schicker, J. Stachel, J.H. Stiller, M.A. Völkl, J. Wilkinson, B. Windelband, M. Winn, A. Zimmermann [und weitere] - Abelev, Betty; Angelov, Venelin; Busch, Oliver; Glässel, Peter; Klein, Jochen; Lohner, Daniel; Lu, Xianguo; Maire, Antonin; Mercado Pérez, Jorge; Oeschler, Helmut; Oyama, Ken; Pachmayer, Yvonne C.; et al. (The European physical journal. C, Particles and fields, 2014)
The inclusive production cross sections at forward rapidity of J / ψ , ψ ( 2 S ) , Υ (1S) and Υ (2S) are measured in pp collisions at √s = 7 TeV with the ALICE detector at the LHC. The analysis is based on a data sample corresponding to an integrated luminosity of 1.35 pb - 1 . Quarkonia are reconstructed in the dimuon-decay channel and the signal yields are evaluated by fitting the μ + μ - invariant mass distributions. The differential production cross sections are measured as a function of the transverse momentum p T and rapidity y , over the ranges 0 < p T < 20 GeV/c for J / ψ , 0 < p T < 12 GeV/c for all other resonances and for 2.5 < y < 4 . The measured cross sections integrated over p T and y , and assuming unpolarized quarkonia, are: σ J / ψ = 6.69 ± 0.04 ± 0.63 μ b, σ ψ ( 2 S ) = 1.13 ± 0.07 ± 0.19 & μ b, σ Υ ( 1 S ) = 54.2 ± 5.0 ± 6.7  nb and σ Υ ( 2 S ) = 18.4 ± 3.7 ± 2.9, where the first uncertainty is statistical and the second one is systematic. The results are compared to measurements performed by other LHC experiments and to theoretical models.